Optimizing the Performance of the Tipidum Unit in Handling Non-Criminal Theft in the Legal Area of the Kediri Police (Indonesian Journal of Police Studies, 2024)
The low Crime Clearance rate of motorcycle theft cases in the Kediri Police Resort is the reason why this research is conducted. The purpose of this research is to describe the performance system of the Tipidum Unit of the Criminal Investigation Unit in the Kediri Police Resort in handling motorcycle theft crimes. In this study, used management theory and organizational resources as tools to dissect the issues in this research. The concepts used are optimization, performance, and handling. This research uses a qualitative method with data collection techniques including interviews, observations, and document studies. The research was conducted at the Kediri Police Resort in accordance with the research subject, namely the Tipidum Unit of the Criminal Investigation Unit in the Kediri Police Resort. The results of this research show that the performance of the Tipidum Unit of the Criminal Investigation Unit in the Kediri Police Resort has not been optimal due to several factors. In the investigation phase, complete administrative procedures have been made, but it is still difficult to find motorcycle theft perpetrators due to the limited evidence such as CCTV recordings. In the prosecution phase, the Tipidum Unit of the Criminal Investigation Unit in the Kediri Police Resort has been equipped with sufficient facilities and infrastructure, but the budget is insufficient to carry out coercive measures. It is hoped that this research can serve as a reference for readers, especially the leaders of the Indonesian National Police (Polri) who handle similar crimes, namely motorcycle theft, so that this research becomes a reference in determining policies and taking steps in resolving motorcycle theft crimes.
Keywords: Optimalisasi kinerja, Unit Tipidum Satreskrim Polres Kediri, Penanganan Tindak Pidana, Curanmor, Penyelidikan, Penyidikan.